1,8-Dihydroxyanthraquinone - Zain, Sharifuddin Md; Ng, S.W. (International Union of Crystallography, 2005)
1,8-Dihydroxyanthraquinone lies on a special position of site symmetry 2; a van der Waals interaction between the 9-carbonyl O atom of one molecule and the 10-carbonyl O atom of another links adjacent molecules into a linear chain [O⋯O = 2.779 (3) Å]. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.